Strengthening Multi-Party Synergy in Handling Efforts Forest and Land Fires in Sumatra and Kalimantan - Dinda Rosanti Salsa Bela (CV. GovPlan Indonesia, 2025)
This study aims to see the extent to strengthen multi-stakeholder synergy, namely the government, the TNI and the National Police in efforts to handle forest and land fires on the islands of Sumatra and Kalimantan in relation to the Presidential Instruction (INPRES) of the Republic of Indonesia Number 3 of 2020 concerning Forest and Land Fire Management. The research method uses the Q-DAS (Qualitative Data Analysis Software) approach with the Nvivo 12 Plus software analysis tool. The research data is a predetermined national mass media activity and the website of the Ministry of Environment and Forestry, namely SIPONGI (Web-Based Forest and Land Fire Control Early Detection Information System) based on a specific period. The results of the study show that there is coordination and synergy carried out by interest actors, namely collaboration between the central government, local governments, the TNI and the National Police. This is evidenced by the various efforts made by the government in handling forest and land fires in Sumatra and Kalimantan. It is strengthened by a drastic decrease in the number of forest and land fire cases that occurred in Sumatra and Kalimantan. In 2020, there was a decrease of 34,749 Ha for the Sumatra region and 26,286 Ha for the Kalimantan region.